ERADICATION OF ILLEGAL FISHING IN INDONESIAN WATERS FROM THE PERSPECTIVE OF INTERNATIONAL LAW - Falah, Ashhabul; Arief, Eva (Journal Philosophy of Law, 2025)
Illegal fishing, or unlawful and unregulated fishing activities, has become a major issue faced by Indonesia as a maritime nation due to its geographical location between the Indian and Pacific Oceans. This activity has negative impacts on the economy, the sustainability of fishery resources, and Indonesia’s marine environment. Numerous arrests of unauthorized foreign vessels that deliberately intrude into Indonesian waters to exploit marine resources highlight the severity of the problem. As Indonesia holds a highly strategic position, it is increasingly vulnerable to various forms of illegal fishing crimes.  This study employs a normative juridical method with a legislative and documentary approach. The data sources include primary data in the form of international legal provisions related to illegal fishing, as well as secondary data obtained from the Ministry of Maritime Affairs and Fisheries. The findings indicate that the eradication of illegal fishing in Indonesian waters, from the perspective of international law, is strictly regulated, particularly under the 1982 United Nations Convention on the Law of the Sea (UNCLOS), which governs state rights within the Exclusive Economic Zone (EEZ) and territorial waters. Indonesia actively participates in various treaties and conventions to combat illegal fishing and collaborates with other nations in these efforts.  Indonesia has encountered fluctuating challenges in its efforts to combat illegal fishing. The relevant authorities enforce strict measures by cooperating with law enforcement agencies and local communities, while the government continuously monitors its waters both independently and in collaboration with other countries. Additionally, the presence of numerous unauthorized activities in Indonesian waters necessitates the involvement of all stakeholders to safeguard the country’s marine and fishery resources from various maritime crimes, particularly illegal fishing.